2018
DOI: 10.3390/app8091486
|View full text |Cite
|
Sign up to set email alerts
|

Emission Behaviors of Inorganic Ultrafine Particles during Zhundong Coal Oxy-Fuel Combustion with Characterized Oxygen Input Fractions Comparable to Air Combustion

Abstract: Zhundong low-rank coal is very likely to be utilized extensively in oxy-fired boilers in the near future. Its PM10 (particulate matter with an aerodynamic diameter of ≤10 μm) emission behaviors during oxy-fuel combustion need to be carefully studied before its large-scale use. The present study examines the emission behaviors of inorganic ultrafine particles (PM0.5, with an aerodynamic diameter of ≤0.5 μm), as well as PM10 during the combustion of Zhundong coal in air and oxy-fuel conditions (O2/CO2) at three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 48 publications
2
11
0
Order By: Relevance
“…The decrease in char temperature in O 2 /CO 2 combustion reduced not only ash vaporization but also particle fragmentation, accounting for the reduction of both types of particles. Similar results have also been observed by other studies with different fuels. ,,− …”
Section: Ash Formation and Deposition In Oxy-pfcsupporting
confidence: 92%
“…The decrease in char temperature in O 2 /CO 2 combustion reduced not only ash vaporization but also particle fragmentation, accounting for the reduction of both types of particles. Similar results have also been observed by other studies with different fuels. ,,− …”
Section: Ash Formation and Deposition In Oxy-pfcsupporting
confidence: 92%
“…Workplace-generated air pollution is critical for workers' and stakeholders' health [68]. Thus, based on the study result, we recommend that the Environmental Protection Bureau prioritize coal-fired power plants as a direction for improvement, which corresponds to the finding to previous studies well [69].…”
Section: Conclusion and Limitationsupporting
confidence: 62%
“…As shown in Figure 8b, its mass fraction distribution had only one peak, located in the ultrafine mode region. For the ultrafine mode PM emitted from the combustion of all four coal samples, all of the mass fractions of Fe were higher, which indicated that Fe was the main component [36]. At a high temperature and under a local reductive atmosphere during the coal combustion, Fe gasified considerably from all of the mineral forms.…”
Section: Effect Of Different From Minerals On Element Composition Andmentioning
confidence: 90%
“…In the studies of PM 10 emissions from Zhundong coal, the yield and composition of PM, the conversion process of one or more minerals to PM, and the influence of combustion parameters have been reported [34][35][36][37]; however, there is still a lack of study from the perspective of the mineral occurrence forms.…”
Section: Introductionmentioning
confidence: 99%